Father's education and children's human capital: evidence from the World War II GI Bill - Marianne Page (University of California, Department of Economics, 2006)
Children who grow up in more highly educated families have better labor market outcomes as adults than those who grow up in less educated families, but we do not know whether this is because education bestows parents with skills that make them better parents or because unobservable endowments that contribute to the parents' education levels are shared by their children. This paper attempts to improve our understanding of the causal processes that contribute to intergenerational mobility by exploiting variation in fathers' education induced by the WWII G.I. Bill. Identificatin rests on the timing of the war: the GI Bill had different effects on different cohorts depending on their likelihood of military service and the probability that schooling had been completed before the war began. I find that a one year increase in a father's education reduces the probability that his child is retained in school by about 2-3 percentage points. This implies that parental schooling levels have an affect on children's outcomes that is independent of their innate ability and suggests that public policies aimed at increasing educational attainment may have important intergenerational effects.
Keywords: 330